Modeling and field-test of a compact electromagnetic energy harvester for railroad transportation. (1st August 2019) - Pan, Yu; Lin, Teng; Qian, Feng; Liu, Cheng; Yu, Jie; Zuo, Jianyong; Zuo, Lei
Highlights: A compact ball screw based design reduces the backlash in the motion transmission. A coupled model is developed to predict the energy harvesting performance. Lab tests are conducted to evaluate harvester and validate the model. Filed tests prove the performance of the harvester under the real condition. Abstract: To enable the smart technologies and safe operation of transit and rail transportation, such as hot box detector, track health monitoring and wireless communication on the railroad side, a cost-effective energy source is in need. This paper presents the design, modeling, in-lab experiment and field-test results of a compact ball-screw based electromagnetic energy harvester with a mechanical motion rectifier (MMR) mechanism for smart railway transportation. The MMR mechanism is realized by the embedded one-way clutches in the bevel gears, which converts the bi-directional track vibration into the unidirectional rotation of the generator. Compared to previous designs, the proposed harvester has reduced backlash and thus can harvest energy from a small input of the track deflection induced by the moving train. Two prototypes with different key design parameters were built and tested. A comprehensive model considering the train-rail-harvester interaction was developed to analyze the dynamic characteristics of the coupled system and predict the energy harvesting performance of the harvesters at different train speeds. Both in-lab and field tests were carried out to examine the energy harvesting performance of the harvesters and validate the model. Field test results illustrated that an average power of 1.12 W and 2.24 W were achieved for two prototypes respectively when a Type A rapid transit passed by with a 30 km/h vehicle speed.